2010
DOI: 10.1158/1940-6207.capr-10-0058
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Inositol Polyphosphate 5-Phosphatase Is an Early Event in Development of Cutaneous Squamous Cell Carcinoma

Abstract: Cutaneous squamous cell carcinoma (SCC) occurs commonly and can metastasize. Identification of specific molecular aberrations and mechanisms underlying the development and progression of cutaneous SCC may lead to better prognostic and therapeutic approaches and more effective chemoprevention strategies. To identify genetic changes associated with early stages of cutaneous SCC development, we analyzed a series of 40 archived skin tissues ranging from normal skin to invasive SCC. Using highresolution array-based… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 23 publications
0
33
1
Order By: Relevance
“…Additional molecular events associated with AK formation include increased activation or levels of SFKs, EGFR, Myc, and ATF-3 (30)(31)(32)(33). In addition, decreased levels of inositol polyphosphate 5′-phosphatase have also been reported in AKs, which could result in increased PI3K/Akt signaling (34).…”
Section: Introductionmentioning
confidence: 99%
“…Additional molecular events associated with AK formation include increased activation or levels of SFKs, EGFR, Myc, and ATF-3 (30)(31)(32)(33). In addition, decreased levels of inositol polyphosphate 5′-phosphatase have also been reported in AKs, which could result in increased PI3K/Akt signaling (34).…”
Section: Introductionmentioning
confidence: 99%
“…Amplifications of epidermal growth factor receptor ( EGFR ) and c-MYC have been identified in AK and cuSCC1011. Loss of INPP5A and CKS1B amplification have been demonstrated in human cuSCC and smaller proportions of AKs1213. Gene signatures that distinguish SCC from AK or irradiated skin have been identified, but they have not been refined to identify a mechanistic basis for progression141516.…”
mentioning
confidence: 99%
“…It was shown that loss of INPP5A was an early event in development of cutaneous squamous cell carcinoma [37]. Speed et al [38] showed that absence or loss of this enzyme activity was also associated with transformation of NRK cells, while Mengubas et al [39] connected decrease of inositol polyphosphate 5-phosphatase activity with several human leukaemias.…”
Section: Discussionmentioning
confidence: 99%